Abdominal Packing for Management of Refractory Postpartum Hemorrhage - I Gde Sastra Winata Winata; Belinda Carlisa; Jessica Nathalia; Ni Nyoman Trijayanti (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2026)
Changes in the demographic and clinical characteristics of pregnant women increase the risk of postpartum hemorrhage, which remains one of the leading causes of maternal mortality in Indonesia. Management of severe postpartum hemorrhage may include abdominal packing. This procedure is performed using a balloon tamponade system combined with gauze-based packing. The fundamental principle of balloon tamponade involves the strategic placement of the tampon within the true pelvis (below the pelvic brim), rather than the false pelvis (above the pelvic brim), to achieve direct physical compression against the pelvic bony boundaries. Following the procedure, patients must be closely monitored, and abdominal tampon removal should be performed in a timely manner, typically within 24–48 hours. Complications associated with abdominal packing may occur if sustained intra-abdominal pressure exceeds 20 mmHg, which can lead to organ failure and necessitate abdominal decompression. However, with adequate monitoring and careful implementation, abdominal packing can serve as a safe and effective alternative for the management of refractory postpartum hemorrhage.